2020
DOI: 10.1088/1361-6595/abad01
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of ‘COST reference microplasma jets’

Abstract: Atmospheric pressure plasmas have been ground-breaking for plasma science and technologies, due to their significant application potential in many fields, including medicinal, biological, and environmental applications. This is predominantly due to their efficient production and delivery of chemically reactive species under ambient conditions. One of the challenges in progressing the field is comparing plasma sources and results across the community and the literature. To address this a reference plasma source… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 119 publications
2
24
0
Order By: Relevance
“…Classical µAPPJs are operated at a single radio frequency of 13.56 MHz. A reference source for the generation of reactive species is the COST micro plasma jet [5,32]. It was developed within the European Cooperation for Science and Technology (COST) action MP1101 'Biomedical Applications of Atmospheric Pressure Plasmas' and is used by various working groups worldwide to ensure the comparability of research results.…”
Section: Introductionmentioning
confidence: 99%
“…Classical µAPPJs are operated at a single radio frequency of 13.56 MHz. A reference source for the generation of reactive species is the COST micro plasma jet [5,32]. It was developed within the European Cooperation for Science and Technology (COST) action MP1101 'Biomedical Applications of Atmospheric Pressure Plasmas' and is used by various working groups worldwide to ensure the comparability of research results.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the uncertainty of the rotational temperature seems to be underestimated by the fit. The temperatures at low input powers are slightly higher than in the COST-Jet, which is most likely due to the increased length of the plasma channel and therefore the longer residence time of the gas in the plasma [31,32].…”
Section: Heatmentioning
confidence: 92%
“…[30,35,36] To limit the effect of impurities in the discharge, gas delivery was regulated via stainless steel tubing. As a reference jet, the COST-Jet is well studied and previous research has reported its reproducibility, [37] gas-phase densities of reactive species, [34,36,38,39] and liquid phase densities, [30,35,[40][41][42] among others. The nozzle of the COST-Jet was placed 4 mm above the liquid surface, see Figure 1.…”
Section: Plasma Setupmentioning
confidence: 99%